2013
DOI: 10.5603/fm.2013.0051
|View full text |Cite
|
Sign up to set email alerts
|

Association between frontal sinus development and persistent metopic suture

Abstract: (Folia Morphol 2013; 72, 4: 306-310)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 19 publications
2
32
1
Order By: Relevance
“…Expansion continues during childhood and reaches its full size after puberty. 23 Each frontal sinus actually consists of 2 independent spaces that develop from different sources. One is developed from the expansion of the ethmoid sinus into the frontal bone, and other is developed from an independent invagination of the middle meatus of the nasal passage; they never coalesce.…”
Section: Discussionmentioning
confidence: 99%
“…Expansion continues during childhood and reaches its full size after puberty. 23 Each frontal sinus actually consists of 2 independent spaces that develop from different sources. One is developed from the expansion of the ethmoid sinus into the frontal bone, and other is developed from an independent invagination of the middle meatus of the nasal passage; they never coalesce.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that in cases of MS persistence, the FSs develop separately on either side of the suture and this entity could be used to differentiate a persistent MS from a fracture of the frontal bone on a radiograph (Bilgin et al, ). Furthermore, the MS precludes the likelihood of development of the sinus beyond the median plane (Davis, ; Schaeffer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is rare to find this suture in adults, its presence is not considered 12 pathological. However, premature closure of any of the cranial sutures results in a pathology known as craniosynostosis and trigonocephaly and is 1,24 termed as metopic synostosis.…”
Section: Discussionmentioning
confidence: 99%
“…The metopic suture is a dentate-type suture between two frontal bones 1 extending from the nasion to the bregma. The frontal bone is a unpaired, median and symmetrical bone that occupies the most anterior part of the cranium forming the forehead which is a common area for scalp & face.…”
Section: Introductionmentioning
confidence: 99%